2023
DOI: 10.1002/anie.202214659
|View full text |Cite
|
Sign up to set email alerts
|

Tunable Multivalent Platform for Immune Recruitment to Lower Antigen Expressing Cancers

Abstract: Chemical immunotherapeutic strategies including Antibody Recruiting Molecules (ARMs ‐ bivalent small molecules containing an antibody‐binding domain (ABD) and a target‐binding domain (TBD)) direct immune‐mediated clearance of diseased cells. Anti‐cancer ARM function relies on high tumor antigen valency, limiting function against lower antigen expressing tumors. To address this limitation, we report a tunable multivalent immune recruitment (MIR) platform to amplify/stabilize antibody recruitment to cells with l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 49 publications
0
8
0
Order By: Relevance
“…Antibody-recruiting polymers contain multiple copies of a hapten ligand along their backbone and allow for binding of anti-hapten antibodies. 23,24 The presence of a second ligand that binds to the surface of cells can mediate ternary complex formation between cell and anti-hapten antibodies, thereby recruiting the latter to the target cell surface. Clustering on the cell surface of endogenous anti-hapten antibodies, such as anti-galactose-a-1,3-galactose, anti-rhamnose and antidinitrophenol antibodies that are present in the blood of most human individuals, triggers destruction of the cell through complement activation and killing by macrophages and NK cells that recognise clustered antibody Fc fragments through their respective Fc-receptors.…”
Section: Introductionmentioning
confidence: 99%
“…Antibody-recruiting polymers contain multiple copies of a hapten ligand along their backbone and allow for binding of anti-hapten antibodies. 23,24 The presence of a second ligand that binds to the surface of cells can mediate ternary complex formation between cell and anti-hapten antibodies, thereby recruiting the latter to the target cell surface. Clustering on the cell surface of endogenous anti-hapten antibodies, such as anti-galactose-a-1,3-galactose, anti-rhamnose and antidinitrophenol antibodies that are present in the blood of most human individuals, triggers destruction of the cell through complement activation and killing by macrophages and NK cells that recognise clustered antibody Fc fragments through their respective Fc-receptors.…”
Section: Introductionmentioning
confidence: 99%
“…This reduces the overall dissociation of the bound therapeutic into the bulk solvent (increased K dapp ). Multivalent immune-binding modalities, however, have been shown to cluster and activate immune proteins/receptors before localization to the target. In the context of tumor immunotherapy, this phenomenon would complicate therapeutic pharmacokinetics and potentially limit applications to direct tumor injection. Additionally, due to rapid microscopic dissociation events, these multivalent modalities may insufficiently stabilize immune cell–tumor cell proximity and synapse formation, to enforce anticancer immune function (e.g., ADCC and ADCP). , Indeed, the effects of rapid microscopic dissociation and rebinding effects on the efficiency of immune receptor activation are currently not well-defined and may not be as effective as a slow microscopic dissociation event (i.e., small k off ) .…”
Section: Introductionmentioning
confidence: 99%
“…A second major current focus in the development of avidity binding probes and molecular therapeutics aims to target multiple receptors on a cell surface simultaneously. This is often done with the goal of selectively clustering and activating biological receptors to affect a specific cellular response, , or targeting a diseased cell that overexpresses a key protein of interest. , Lake et al reported the development of multivalent tumor targeting chimeras that efficiently recruit serum antibodies to the surface of tumor cells, with the goal of inducing antitumor immune responses . These chimeras consisted of multiple tumor antigen and serum antibody binding ligands decorating a polymer backbone, and were observed to bind tumor cells with significantly longer residence times, compared to monovalent chimera analogues (Figure ).…”
mentioning
confidence: 99%
“…Multivalent chimera strategy using avidity to enhance immune recognition of tumor cells. Reproduced with permission from ref . Copyright 2023 John Wiley & Sons.…”
mentioning
confidence: 99%
See 1 more Smart Citation